INTEGRASI NILAI-NILAI MULTIKULTURALISME DALAM PEMBELAJARAN UNTUK MEMBANGUN TOLERANSI DI LINGKUNGAN MIN 1 LABUHANBATU - Ika Sundari; Kholidah Hannum Hasibuan; Rizki Hafni Rambe; Silvia Anggraini Hasibuan (UIN Sumatera Utara Medan, 2024)
The cultural diversity within the environment of MIN 1 Labuhanbatu, where students and teachers come from various ethnic backgrounds such as Javanese, Mandailing, and Malay, creates an urgent need to integrate multicultural values into the learning process. This study analyzes the efforts and impacts of integrating multicultural values in fostering student tolerance. The research methods employed include observation, interviews, and document analysis. The findings reveal that teachers at MIN 1 Labuhanbatu have implemented various approaches, such as introducing local culture through Projek Penguatan Profil Pelajar Pancasila dan Rahmatan lil Alamin (P5RA), utilizing multicultural-based teaching materials, conducting collaborative cross-cultural activities, and celebrating national and religious holidays. These approaches effectively enhance students’ awareness of the importance of living harmoniously, reduce potential conflicts, and create an inclusive learning environment. However, challenges remain in maintaining social harmony, particularly in managing cultural and value differences. Therefore, integrating multicultural values becomes a key strategy to foster tolerance, strengthen solidarity, and establish harmony amidst diversity.